2010
DOI: 10.2174/157340610793358909
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and In Vitro Evaluation of Some Isatin-Thiazolidinone Hybrid Analogues as Anti-Proliferative Agents

Abstract: A range of isatin-thiazolidinone hybrid analogues were synthesized and their cytotoxicity was evaluated against several cancer cell lines in vitro. The acute toxicity studies in mice models revealed that these analogues possess low systemic toxicity and are safe up to 1600mg/Kg. Among the compounds synthesized, 5-(2-nitrobenzylidene)-2-(isatin-3-azino)-thiazolidin-4-one (CI) has been shown to be the most active, highly promising compound which induced S phase arrest in cell cycle in a time dependent manner. Ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(13 citation statements)
references
References 20 publications
1
12
0
Order By: Relevance
“…Interestingly, compound 5i, possessing 5-methylindolin-2-one ring and phenyl ring without substitutions, exhibited the most potent cytotoxicity against MDA-MB-231 cancer cell line. Therefore, we tentatively concluded that the electronic influences of the substituent in the phenyl ring appear to play an important role in activity, and this behavior depends on the cancer cell lines to which they are In the present study, the coupling between indolin-2-one and 5-benzylidene-4-thiazolidinone systems led to several compounds with better anticancer activity than the previously reported analogues [15,23,24]. Two neutral conjugate systems integrated at the 4-thiazolidinone moiety may contribute to the anticancer activity of these compounds, which has already been partially confirmed by anticancer activity of the rhodacyanine dyes [25].…”
Section: Biological Results and Discussionsupporting
confidence: 57%
“…Interestingly, compound 5i, possessing 5-methylindolin-2-one ring and phenyl ring without substitutions, exhibited the most potent cytotoxicity against MDA-MB-231 cancer cell line. Therefore, we tentatively concluded that the electronic influences of the substituent in the phenyl ring appear to play an important role in activity, and this behavior depends on the cancer cell lines to which they are In the present study, the coupling between indolin-2-one and 5-benzylidene-4-thiazolidinone systems led to several compounds with better anticancer activity than the previously reported analogues [15,23,24]. Two neutral conjugate systems integrated at the 4-thiazolidinone moiety may contribute to the anticancer activity of these compounds, which has already been partially confirmed by anticancer activity of the rhodacyanine dyes [25].…”
Section: Biological Results and Discussionsupporting
confidence: 57%
“…Several research groups adopted hybridization approach for the design of isatin-thiazolidine/thiazolidinone hybrid analogues as potent antiproliferative agents [22][23][24][25][26]. Lee and co-workers reported two studies about the design, synthesis and cytotoxicity evaluation of two different series of isatin-benzothiazole and isatin-linked chalcones analogs against three human breast cancer cell lines.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Indole compounds have recently become a hot topic in the study of antitumor drugs because of their low toxicity . ISA is a monomer of indirubin, which is an antitumor drug developed in China for the clinical treatment of chronic myelocytic leukemia .…”
Section: Discussionmentioning
confidence: 99%